HUBUNGAN FLEXIBILITAS TUBUH DAN KECEPATAN DENGAN PRESTASI LOMPAT JAUH PADA SISWA PUTRA KELAS X MAN 2 PRAYA KABUPATEN LOMBOK TENGAH TAHUN PELAJARAN 2017/2018 - Muhammad Aden; Subakti Subakti; Andi Anshari Bausad (Universitas Pendidikan Mandalika, 2017)
Based on the result of preliminary observation on MAN 2 Praya students of Central Lombok regency, most students did not have the physical ability to make leaps which impact on the low result of long jump. This study aims to determine the correlation between body flexibility and speed toward the achievement of long jump. The researcher conducted the research for 3 (three) days, i.e. from August 1 to August 3, 2017 on class X students at MAN 2 Praya Central Lombok with the sample of 24 students taken by using proportional random sampling. The method of data collection is used documentation and performance test. The instruments used in the study are box sit-and-reach and a 50-meter run speed test conducted directly in the field. The data obtained was then analyzed by using the formula of product moment correlation. The result of data obtained (r-score = 0.515) was higher than (r-table = 0.404) for 5% significant level with N = 24. The data obtained by statistic showed that there is positive and significant correlation between the body flexibility and speed toward the achievement of long jump on the students of class X at MAN 2 Praya Central Lombok in 2017/2018 academic year. It can be concluded that the null hypothesis (Ho) is rejected, while the alternative hypothesis (Ha) is received. It can be stated that there is correlation between the body flexibility and speed toward the achievement of long jump on the students of class X at MAN 2 Praya Central Lombok in 2017/2018 academic year